2011
DOI: 10.1007/s00592-011-0275-z
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of depression, anxiety, and cognitive function in patients with type 2 diabetes

Abstract: To evaluate the prevalence of depression in outpatients with type 2 diabetes and its possible correlation with anxiety, cognitive function, and clinical variables. The Zung Self-Rating Depression and Anxiety Scales and the Mini-Mental-State Examination were administered to 249 non-insulin-treated (NIT) and 249 insulin-treated (IT) outpatients with type 2 diabetes, aged 40-80, in a cross-sectional survey. Compared with a reported prevalence of 6-13% in the general population, 104 (20.9%) patients had either a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 26 publications
3
32
1
2
Order By: Relevance
“…Nevertheless, our study showed a prevalence of depression of 18.6%, which was essentially comparable to that recently reported in a recent large meta-analysis including patients with T2D [29]. Furthermore, the prevalence of psychological symptoms herein reported was comparable to previous estimates by Trento et al in a cohort of Italian T2D patients [30]. Despite the sample size of our study was sufficiently large to detect reasonable estimates of anxiety, depression and diabetes-related distress, we recognize as a further, potential limitation that it was conducted in a single diabetes center, which might affect the generalizability of our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, our study showed a prevalence of depression of 18.6%, which was essentially comparable to that recently reported in a recent large meta-analysis including patients with T2D [29]. Furthermore, the prevalence of psychological symptoms herein reported was comparable to previous estimates by Trento et al in a cohort of Italian T2D patients [30]. Despite the sample size of our study was sufficiently large to detect reasonable estimates of anxiety, depression and diabetes-related distress, we recognize as a further, potential limitation that it was conducted in a single diabetes center, which might affect the generalizability of our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to other industrialized countries, the social security system in Italy provides free access to eye care services, such as screening, assessment and treatment for diabetic 8 retinopathy, although in many instances visits are carried out on a fee-for-service basis. However, health care systems too often underestimate the problems that may arise in the quality of life of patients (21), especially in view of the tendency of diabetes to associate with depression (22). The projected increasing prevalence of STDR and visual impairment (23) and the associated reduction in functional status and independence, will greatly increase the resulting burden of this complication of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety also has been found to be associated with age among individuals with diabetes, although the association becomes weaker with increasing age [37]. In addition, anxiety has been found to be associated with lifetime severe hypoglycemia, but not abdominal obesity or cardiovascular disease, in longitudinal analysis [38].…”
Section: Association Between Anxiety and Diabetes Outcomesmentioning
confidence: 98%